FORMULATION AND EVALUATION OF ECONAZOLE NITRATE NANOEMULSION FOR TOPICAL OCULAR ADMINISTRATION - KUMAR J., NANDHA; PATIL, ANASUYA; G., HEMANTH (International Journal of Applied Pharmaceutics, 2025)
Objective: The study aimed to use cold homogenization to create an Econazole Nitrate (ECN) nano-emulsion formulation. Methods: Different ratios of surfactants (polypropylene 188 and Tween 80) and co-surfactants (ethanol) were used to create eight formulations. Out of them, compositions ECN1, ECN4, ECN5, and ECN7 were chosen due to initial research demonstrating encouraging outcomes. Dissolution studies evaluated droplet size, shape, drug content, and in vitro drug release characteristics. A comparative analysis was conducted to assess the improvement in medication release rates compared to pure drug formulations. Results: ECN5, which attained an 89.43% drug release rate after 360 min, demonstrated the greatest medication release rate among the chosen formulations (ECN1, ECN4, ECN5, and ECN7). The improved formulations showed consistent spherical forms with droplet diameters ranging from 114 nm to 214.87 nm. Based on these findings, it appears that the nano-emulsion formulation successfully raises econazole nitrate's solubility, which is important because of its poor solubility in ocular administration applications. Conclusion: The study used cold homogenization to effectively generate and optimize ECN nano-emulsion formulations. The most promising features of formulation ECN5, such as consistent droplet size distribution and dramatically improved drug release rates, were displayed. These results demonstrate the potential of nano-emulsions to enhance econazole nitrate's solubility and delivery effectiveness, especially for ocular applications.